Pengembangan Sistem Informasi Manajemen Alat Laboratorium (Studi Kasus Laboratorium Fisika Tanah Fakultas Pertanian Universitas Brawijaya) - Mohamad Ilham Ridho; Djoko Pramono; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Soil Physics Laboratory is one of five laboratories that are located in Soil Major, Faculty of Agriculture, Brawijaya University. The objective of this laboratory is to support laboratory practicum and Soil students' research. Management of laboratory equipment inventory, laboratory equipment loan data, laboratory equipment loan return, and credit score is still done manually via microsoft word, microsoft excel, and paper. The problem is the laboratory assistant is in difficulty to recap forms and documents because it is still done manually. Based on the known problems, laboratory equipment management information system is needed so it will ease the laboratory assistant's work in the management of equipment inventory, equipment loan, and credit score. This research uses Software Development Life Cycle (SDLC) Waterfall, so the process of development can be done easier and gradually. Requirement analysis and design phase generates UML diagrams. The framework that is used on the implementation phase is CodeIgniter 4. Result of the validation testing shows that all the features of the system can be run well and valid. Compatibility testing's result shows that the system doesn't have any compatibility problems on various browsers. Result of SUS shows that the final grade of usability is good and can be accepted by all actors.